Comparison of objective visual quality between SMILE and FS-LASIK in moderate-to-high myopia - Zou, Huaxian; Wei, Xianxian; Li, Lili; Wei, Diefeng; Mao, Hejuan; Huang, Yanyan; Lu, Pengfei; Li, Ziyu; Zhong, Dedong; Chen, Qi (Frontiers in Medicine, 2024)
Purpose This study aims to compare the changes in the corneal wavefront aberrations and the objective visual quality resulting from two types of eye surgery—small incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK)—in patients with moderate-to-high myopia. Methods A prospective analysis was performed on 98 eyes of 51 patients who underwent SMILE. Additionally, 88 eyes of 45 patients who underwent FS-LASIK were analyzed. All patients underwent ocular examination preoperatively and at 1 day, 1 week, 1 month, and 3 months postoperatively. Corneal aberrations and objective visual quality were measured using the Optical Quality Analysis System II (OQAS II) and Optical Path Difference Scan III (OPD-Scan III). Results At postoperative 1 day and 1 week, there was a statistically significant difference in uncorrected distance visual acuity (UDVA) between SMILE and FS-LASIK (P < 0.05). Postoperative spherical (S), cylinder (C) and spherical equivalent refraction (SE) were similar between the two groups (P > 0.05). In both groups, the absolute magnitude of total higher-aberrations (tHOA), piston, vertical tilt, vertical coma, and spherical aberration (SA) increased after surgery compared to preoperative values (P < 0.05). There was no significant difference in Δhorizontal tHOA, Δhorizontal tilt, Δhorizontal coma, and Δhorizontal trefoil between the two groups (P > 0.05), and the FS-LASIK had higher Δvertical trefoil and ΔSA (P < 0.05) but lower Δpiston, Δvertical tilt, and Δvertical coma than the SMILE group (P < 0.05). There was a rise in objective scattering index (OSI) and a decline in both modulation transfer function (MTF) cutoff and Strehl ratio (SR) after surgery compared to preoperative values in both groups (P < 0.05). There was a statistically significant difference in the OSI at 1 day and 3 months between the two groups (P < 0.05). Postoperative MTF cutoff and SR were similar between the two groups (P > 0.05). Postoperative OSI was positively correlated with corneal tHOA (0.261 ≤ R ≤ 0.483, P < 0.05) and was negatively correlated with vertical tilt and vertical coma (−0.315 ≤ R ≤ −0.209, P < 0.05) in both groups. Conclusion While both SMILE and FS-LASIK can effectively correct moderate-to-high myopia, there is an increase in corneal aberrations and a postoperative delay in objective visual quality. The cornea may require a longer recovery period in the SMILE. OPD-Scan III combined with OQAS II is a useful supplementary inspection for assessing the optical quality following refractive surgery.